A screening framework for pesticide substitution in agriculture. (10th August 2018) - Steingrímsdóttir, María Magnea; Petersen, Annette; Fantke, Peter
Abstract: Farmers lack science-based tools to flexibly and rapidly identify more sustainable pesticides. To address this gap, we present a screening-level substitution framework to compare and rank pesticides using a consistent set of indicators including registration, pest resistance, human toxicity and aquatic ecotoxicity impact potentials, and market price. Toxicity-related damage costs and application costs were combined with application dosages to yield total costs per pesticide. We applied and tested our framework in a case study on pesticides applied to lettuce in Denmark. Our results indicate that by ranking pesticides within each target class (e.g. fungicides) the most suitable pesticide can be identified based on our set of indicators. As an example, in the insecticide scenario, pymetrozine performs best with total costs of 23 €/ha, while dimethoate and pirimicarb, which are also on the EU candidate substitution list, performed worst. Total costs across considered pesticides range from 23 to 302 €/ha. Our framework constitutes an operational starting point for identifying sustainable pesticides by farmers and other stakeholders and highlights (a) the need to consider various relevant aspects influencing the ranking of pesticides and (b) the importance of combining total cost performance per pesticide unit applied with respective application dosage per hectare as both may vary greatly. Future research should focus on considering additional indicators (e.g. terrestrial ecotoxicity), increasing resistance-related data, and reducing uncertainty that is mainly related to emission and toxicity impact estimates. Highlights: A novel framework for the substitution of agricultural pesticides is presented. A case study of pesticides applied to lettuce in Denmark was developed. Results show costs from toxicity related damages and application practice. Both costs per unit application and application amount per hectare are relevant.